Robotic-assisted percutaneous coronary intervention: experience in Switzerland - Häner, Jonas D.; Räber, Lorenz; Moro, Christina; Losdat, Sylvain; Windecker, Stephan (Frontiers in Cardiovascular Medicine, 2023)
Aims of the study: Percutaneous coronary intervention (PCI) exposes operators to ionizing radiation. Robotic-assisted PCI (RA-PCI) is a novel technology that enables interventional cardiologists to operate coronary devices remotely from a radiation-shed cockpit. The aim of this study is to describe the experience and challenges during the initiation of a RA-PCI program and to report outcomes of the first 21 patients undergoing RA-PCI in Switzerland. Methods: All patients undergoing RA-PCI using the CorPath GRX Vascular Robotic System between 06/2021 and 12/2021 at Inselspital, Bern University Hospital were included in this retrospective registry study. Baseline, procedural and clinical follow-up data were prospectively assessed as part of the Cardiobase Bern PCI registry (NCT02241291). The two endpoints of interest were clinical success (defined as <30% residual diameter stenosis in the absence of in-hospital major adverse cardiovascular events [MACE: composite of death, periprocedural myocardial infarction, target-vessel revascularization, and stroke]) and robotic success (defined as clinical success and completion of RA-PCI without or with partial manual assistance). Additional outcome measures include clinical long-term outcomes at one year. Results: Twenty-five lesions in 21 patients were treated with RA-PCI (age 62.4 ± 9.1 years, 24% female). Clinical success was achieved in 100%, and robotic success in 81% (17/21 procedures, including 4 procedures requiring partial manual assistance). Manual conversion (e.g. manual completion of the procedure) occurred in 19% (4 procedures). Reasons for manual assistance or conversion were poor guiding-catheter back-up or platform limitations (4), adverse events (2x transient slow-flow that was solved manually), safety decision (1x vasovagal reaction not related to robotic approach), and software error (1). No in-hospital MACE occurred. During 12 months of follow-up, one patient suffered a non-target-vessel myocardial infarction requiring repeat PCI. Conclusions: RA-PCI can safely be performed without clinically relevant robot-associated complications in selected patients with approximately 80% of procedures conducted without or with partial manual assistance.